Making sense: the academic journeys of women with learning disabilities - Blansett, Catherine Mary, author; Lehmann, Jean P.; Deniston, Terry L., committee member; Banning, James H., committee member; Schatz, Mona C. S., committee member (Colorado State University. Libraries, 2004)
Postsecondary education for all students with disabilities has been encouraged by the trend to meet workforce demands, as well as legislation in support of education and the civil rights of children and adults with disabilities. Consequently, more women with learning disabilities are attending four-year public research universities. This qualitative study was undertaken to understand their academic success. Thirteen women with learning disabilities who have attained the success of at least junior standing at a four-year public research university in the Southwest volunteered to share their academic journeys. Study participants are of varying ages, backgrounds, and differing disability labels. While participants differ greatly, still, themes run through their experiences that describe their paths to academic success. Their extraordinary honesty provides insight into how they compensate, from a very early age, when their perceptions of their experiences do not meet their expectations. Furthermore, their stories explain how they come to terms with this dissonance. Participant accounts portray a dynamic process that explains their journey, a process that helps them make sense of their experiences and allows them to move forward toward their goals.
Keywords: higher education; special education